2021
DOI: 10.1080/10298436.2020.1866760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of replacing virgin bitumen by plastic waste in asphalt concrete mixtures

Abstract: Polymers are used worldwide for their unique properties such as a light weight or chemical resistance, but which have led to an environmental challenge because of the time they need to completely decompose when buried in landfills.Complementarily, bitumen generates the second biggest environmental impact in the construction of a road. This paper analyses the mechanical, environmental and economic performance of replacing 25% of bitumen with two low-cost plastic wastes (cable plastic and the film fraction from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Asphalt mixtures with PE added through the dry process have greater increase in environmental impacts relative to the HMA baseline ( 43 ). Lastra-González et al ( 44 ) evaluated asphalt mixtures with binder modified with 25% of PE recycled from copper cables and flexible packaging film. Their LCA evaluated end-point indicators and revealed that modified mixtures could be environmentally beneficial compared with control HMA and that service life extension increased the benefits ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asphalt mixtures with PE added through the dry process have greater increase in environmental impacts relative to the HMA baseline ( 43 ). Lastra-González et al ( 44 ) evaluated asphalt mixtures with binder modified with 25% of PE recycled from copper cables and flexible packaging film. Their LCA evaluated end-point indicators and revealed that modified mixtures could be environmentally beneficial compared with control HMA and that service life extension increased the benefits ( 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lastra-González et al ( 44 ) evaluated asphalt mixtures with binder modified with 25% of PE recycled from copper cables and flexible packaging film. Their LCA evaluated end-point indicators and revealed that modified mixtures could be environmentally beneficial compared with control HMA and that service life extension increased the benefits ( 44 ). It is noteworthy, however, that Lastra-González et al ( 44 ) accounted for the avoided burden of plastic incineration when PE is recycled and used as an asphalt modifier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lastra-González et al [63] observed increased permanent deformation by adding polyethylene (PE) and polypropylene (PP) to the asphalt mixture, whereas polystyrene (PS) reduced the resistance. Lastra-González et al [64] and others [7,22] also found improvements in rutting resistance with plastic film (LDPE) incorporation using a wheel-tracking test at 60 • C.…”
Section: Resistance To Permanent Deformationmentioning
confidence: 91%
“…The results indicate that the waste PP asphalt mixture is more eco-friendly compared with the SBS asphalt mixture. Two highly modified asphalt mixtures, replacing 25% of bitumen with two types of plastic waste, show environmental and economic advantages; specifically, a 17% reduction in environmental impact and an 11% reduction in economic impact can be achieved [ 150 ].…”
Section: Engineering Properties Environmental Concerns and Practical Engineering Applications Of Waste Plastic Asphalt Mixturesmentioning
confidence: 99%